Pengoptimalan Ruang Pasar Rakyat Kota Batu (Program Studi Arsitektur Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2022)
Batu City, where most of its residents are farmers, vegetables and fruits are abundant but have not been managed optimally. The market in Kota Batu is still not feasible because the spatial arrangement has not been maximized and the supporting facilities are inadequate, with this study aimed at developing market design concepts namely